2021
DOI: 10.3390/nu14010125
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Perceptions of Child Diet Quality: What Influenced Their Judgment

Abstract: This study aimed at assessing the correctness of a caregiver’s perception of their child’s diet status and to determine the factors which may influence their judgment. 815 child-caregiver pairs were recruited from two primary schools. 3-day 24-h recall was used to evaluate children’s dietary intake, Chinese Children Dietary Index (CCDI) was used to evaluate the dietary quality. Multivariate logistic regression models were used to explore the factors that could influence the correctness of caregiver’s perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…In Ethiopia, a study done by Berhane et al ( 2018 ) reported that caregivers were aware that consuming unhealthy foods affects health and contributes to the development of some diseases. Similarly, in China, according to the study done by Shao et al ( 2022 ), caregivers were aware that poor diets can lead to overweight and obesity, while in Bangladesh, a study done by Rahman et al ( 2016 ) reported that caregivers perceived that healthy foods do not taste as good as unhealthy foods. The Arabian study done by Ismail et al ( 2022 ) reported that caregivers indicated that foods that are low in fibre can cause health issues and can lead to diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, a study done by Berhane et al ( 2018 ) reported that caregivers were aware that consuming unhealthy foods affects health and contributes to the development of some diseases. Similarly, in China, according to the study done by Shao et al ( 2022 ), caregivers were aware that poor diets can lead to overweight and obesity, while in Bangladesh, a study done by Rahman et al ( 2016 ) reported that caregivers perceived that healthy foods do not taste as good as unhealthy foods. The Arabian study done by Ismail et al ( 2022 ) reported that caregivers indicated that foods that are low in fibre can cause health issues and can lead to diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we examined whether the membership of a given group is associated with the participants' demographic characteristics, such as occupation, kinship, or the sex and age of the children. As there is evidence that the educational level, living area, and family type might influence children's HLH [11,25,42,45,[55][56][57][58][59][61][62][63][64], we expected caregivers with the most positive attitudes towards HLHs to live in rural communities, have a high level of education, and not be part of single-parent families. However, we did not expect that the sex or age of the children were related to the caregiver's membership in a given cluster [14,45,46,[57][58][59].…”
Section: The Present Studymentioning
confidence: 99%
“…Similarly, children of highly educated parents consume milk, fruits, and vegetables more frequently, engage in more physical activity, and spend fewer hours in front of the TV screen [55,63]. This is associated with more educated caregivers being more likely to correctly perceive diet quality [64] and to favor habits, such as not having television in the children's room, that avoid excessive hours in front of screens [59].…”
Section: Introductionmentioning
confidence: 99%